DINAMIKA IMPULSE BUYING DI MR.DIY CITIMART BITUNG: PERAN STORE ATMOSPHERE DAN HEDONIC SHOPPING VALUE DALAM MEMBENTUK KEPUTUSAN PEMBELIAN PELANGGAN - Tooy, Stephanie Mervin; Supandi Soegoto, Agus; Ramenusa, Oktaviani; Salindeho, Yefta (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The purpose of this study is to investigate how hedonic shopping value and store atmosphere affect impulsive buying behavior among MR.DIY Citimart customers in Bitung. Impulse buying refers to rush, unplanned purchases that are driven by environmental cues, like a store's atmosphere, and the emotional benefits of shopping. Total of 99 respondents were given questionnaires as part of this study's quantitative descriptive methodology. The findings demonstrate that hedonic shopping value and store atmosphere both have a major impact on impulsive purchases. In particular, hedonic shopping value contributes 8.7% and store atmosphere increases impulse buying by 26.2%. The study emphasizes how crucial it is to create a fun retail space and provide a pleasurable shopping experience in order to encourage impulsive purchases. Retailers can use these findings to improve customer engagement and sales by refining their strategies.